Adoption and Impact of Drought-Tolerant Varieties, RiceAdvice app, Mechanization, and Climate Information Services on Welfare Indicators of Farmers in Mali - Suh, Neville; Diallo, Aboubacar; Dossou-Yovo, E. R (2024)
The AICCRA project in Mali aims to improve climate resilience through climate-smart agriculture (CSA) and climate information services (CIS). Between 2021 and 2024, the project reached 310,333 rice farmers (107,846 males, 202,487 females), providing climate information services, 6,124 farmers received drought-tolerant rice varieties (4,611 females, 1,513 males), 41,596 used the RiceAdvice app (23,607 males, 17,989 females), and 17,165 received mechanization services (9,784 males, 7,381 females). The project evaluated the impacts of these interventions on farm households' welfare indicators, including yield, income, and food security. The results showed significant benefits for adopters. Users of CIS experienced a 2,363 kg/hectare increase in rice yield, 778,788 FCFA increase in income, and a food consumption score of 12. Drought-tolerant rice adopters saw a 1,280 kg/hectare yield increase, 712,868 FCFA income increase, and a score of 10. RiceAdvice app users had a 1,992 kg/hectare yield increase, 191,500 FCFA income increase, and a score of 16. Mechanization users saw a 1,703 kg/hectare yield increase, 384,749 FCFA income increase, and a score of 22. The findings underscore the importance of promoting CSA and CIS programs to enhance climate resilience in Mali and beyond.